2009
DOI: 10.1111/j.1741-3729.2009.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Adolescents' Family Caregiving: Selection Effects and Longitudinal Associations With Adjustment

Abstract: One hundred ten Mexican American adolescents (12 – 17 years) who provide infant care for their older sisters were studied to determine the effects of family caregiving responsibilities on adolescents’ adjustment. Controlling for prior adjustment and family context factors, providing many hours of caregiving predicted an increase in youths’ school absences and disciplinary problems. Frequent conflict surrounding caregiving was associated with increased stress and depression and lower school grades. Older girls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 46 publications
(90 reference statements)
2
56
3
Order By: Relevance
“…However, familism did not protect Mexican-Americans in the risk context of economic hardship, discrimination, acculturative stress, family stress, or family conflict (Delgado et al 2011;East and Weisner 2009;Umaña-Taylor et al 2011). Family functioning, a related construct composed of effective discipline practices, family structure, and family cohesion, was not found to be protective for African American and Hispanic adolescents in the context of stressful life events (Tolan et al 2013).…”
Section: Familismmentioning
confidence: 97%
See 2 more Smart Citations
“…However, familism did not protect Mexican-Americans in the risk context of economic hardship, discrimination, acculturative stress, family stress, or family conflict (Delgado et al 2011;East and Weisner 2009;Umaña-Taylor et al 2011). Family functioning, a related construct composed of effective discipline practices, family structure, and family cohesion, was not found to be protective for African American and Hispanic adolescents in the context of stressful life events (Tolan et al 2013).…”
Section: Familismmentioning
confidence: 97%
“…Among family factors, maternal support buffered girls more strongly than boys (Vaughan et al 2010), whereas maternal closeness protected boys but not girls against depression (Hammack et al 2004). The disparate findings might be due to the differences in risk context, A few studies may have lacked sufficient power to detect gender differences in interactions between protective and risk factors (e.g., Chung and Docherty 2011;East and Weisner 2009;Polanco-Roman and Miranda 2013), but the majority of studies not reporting significant gender differences employed quite large samples (up to N = 7863). Whereas there is insufficient evidence to explain these differences, on the whole it seems that there are relatively few gender differences in protective mechanisms.…”
Section: Gender Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although attitudinal and behavioral familism can often be protective, it can also result in detrimental outcomes in stressful contexts acting as a potentiating factor. East and Weisner (2009) found that extensive family responsibilities predicted adolescent stress, internalizing symptoms, and worse school outcomes, and familism did not buffer against the detrimental effects of extensive caregiving in the context of sibling teenage parenting. Similarly, in their study of suicidal adolescents ( Nolle, Gulbas, Kuhlberg, & Zayas, 2012), participants sacrificed their material needs or subjugated their emotions to avoid unduly burdening their families, and when they failed to fulfill their obligations, they felt that sacrificing themselves through suicide would serve as an appropriate solution.…”
Section: Psychosocial and Academic Outcomesmentioning
confidence: 99%
“…More work needs to examine the differential impact of both aspects of familism, with a specific focus on the intersection of the two as the review finds that both attitudinal and behavioral familism can pose a threat to psychological and academic functioning ( East & Weisner, 2009;Nolle et al, 2012;Sánchez et al, 2010). Because these studies all utilized different methodology, it is difficult to draw firm conclusions, but it is likely that attitudinal and behavioral factors serve as both risk and protective factors and this relationship depends both on the type of familism in question as well as contextual factors (e.g., Calzada et al, 2013).…”
Section: Attitudinal Versus Behavioral Familismmentioning
confidence: 99%